Philanthropic Perspective: Reading Muhammadiyah’s Social Activism Among Earthquake Survivors - Alifuddin, Muhammad; La Djamudi, Nadir; Samritin (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
This research on Muhammadiyah's Social Activism for West Sulawesi Earthquake Survivors aims to analyze it analytically and map Muhammadiyah's social activities from a philanthropic perspective. This research data was obtained through observation, in-depth interviews and document review. All data obtained were analyzed using the Miles and Huberman paradigm combined with Von Eckarberg's hermeneutic phenomenological analysis model. The findings and discussion of this research conclude the following: Muhammadiyah Sultra's social activism for earthquake survivors can be categorized as social philanthropy. This can be seen from the movement of volunteers who not only provide compensation but also carry out empowerment activities in the form of strengthening the spiritual and intellectual capacity of survivors. Muhammadiyah's social activism towards survivors is carried out on universal humanitarian principles and relies on the theological ideas of al-ma'un and Islam rahmatan lil alamin, so that the various social services and capacity strengthening programs carried out during the emergency response period are not co-opted by the social, cultural and religious background of the survivor group as subjects who receive social services.